2018
DOI: 10.31219/osf.io/83exy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water consumption as a source of error in the measurement of heart rate variability

Abstract: Abstract.Heart rate variability (HRV) is a common measure of the autonomic modulation of the heart. To ensure accuracy, various external factors known to affect HRV such as medication use and concurrent illnesses are frequently controlled during measurement. While the influences of such confounds on accurate measurement of HRV are accepted, the influence of seemingly innocuous daily activities such as drinking and eating have received remarkably little attention. In fact, water consumption is known to provoke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Monnard and Grasser observed a similar decrease in HR up to 45 min with no alterations to CO, however they observed an immediate decrease in SBP following water (335 mL) consumption [ 38 ]. The extended response of HR in the current study may be due to a dose dependent response considering that our dosage of fluid (1 L) was higher and ingested across a greater time frame (i.e., 30 min) than previous studies [ 18 , 40 ]. Grasser et al found a prolonged depression in HR following the ingestion of 800 mL of water for up to 60 min when compared to 200, 400, and 600 mL [ 18 ].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Monnard and Grasser observed a similar decrease in HR up to 45 min with no alterations to CO, however they observed an immediate decrease in SBP following water (335 mL) consumption [ 38 ]. The extended response of HR in the current study may be due to a dose dependent response considering that our dosage of fluid (1 L) was higher and ingested across a greater time frame (i.e., 30 min) than previous studies [ 18 , 40 ]. Grasser et al found a prolonged depression in HR following the ingestion of 800 mL of water for up to 60 min when compared to 200, 400, and 600 mL [ 18 ].…”
Section: Discussionmentioning
confidence: 68%
“…While interpreting the findings of the current study, it is important to note the current study design differed from others as it did not include a baseline measure of cardiovascular parameters prior to fluid consumption [ 19 , 23 , 38 , 39 , 40 ]. Instead, the first measurement of cardiovascular and fluid composition was obtained immediately following fluid ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Portable short-duration HRV assessment methods of~1-5 min have been demonstrated to be effective [11,13]. However, factors such as the choice of HRV measures (e.g., root mean square of sum of differences (RMSSD)), measurement position (e.g., supine, seated, standing), water intake prior to measurement, sex, time of measure (e.g., nocturnal, upon awakening, upon arrival at training or after submaximal exercises) and breathing rate may all affect HRV measures [11,[14][15][16]. Of particular interest for coaches is if there are differences between HRV measures taken upon awakening (which are recommended as best practice when using heart rate measures to guide training prescription) [17] and measures taken upon arrival at training (which may be preferred by coaches for compliance reasons) [18].…”
Section: Introductionmentioning
confidence: 99%
“…While we controlled for medication use and comorbidities known to impact HRV, it is possible that the signal may have been affected by variables that were uncontrolled, such as smoking (Kemp, Koenig & Thayer, 2017;Murgia et al, 2019), body mass index (Föhr et al, 2016;Koenig et al, 2014), physical activity (Kemp et al, 2017;May, McBerty, Zaky & Gianotti, 2017), and alcohol (Ralevski, Petrakis & Altemus, 2019) and water (Heathers et al, 2018) consumption.…”
Section: Discussionmentioning
confidence: 99%